Make the Cities Work: Some Stories of Smart City Initiatives Around the Globe - Sukmo Pinuji; Wahyuni Wahyuni (BHUMI: Jurnal Agraria dan Pertanahan, 2019)
The concept of Smart City (SC) has been popular recently, and has been adopted by many cities in the world with various implementation and development. As the world most population now concentrates on urban area, a sustainable city planning and management become important. As the population keeps growing,pressure and tension on a city arise: space for living, waste management, traffic congestion, sufficient clean water resources, and other issues. Beginning in around 2009, the concept of SC was designed to solve problems related to city growth in a sustainable manner. By using technology, Internet of Things (IoT), and community participation, SC aims to make the city a livable place for its inhabitants, putting people as the center of interest and in quality of life in sustainable manners as ultimate goal. This paper aimed to deliver a study on the trend of SC adopted by two cities: Amsterdam and Jakarta. The study was conducted through literature review. The data were analyzed to compare the concept of SC in each city from different parameters, focusing on the developmentprocess, technological adoption, political and institutional arrangement and implementation. The results show that each city has specif ic strategy to implement SC, based on their economic, social, environment and demographic characteristics. It is also important to underline that the main concept of SC is to attract related stakeholders in taking charge of their roles for the success of SC. Furthermore, both cities has a sharing vision in putting environment as the main framework of the development of SC.